2005
DOI: 10.1074/jbc.m414407200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heparin Affin Regulatory Peptide Signaling in Human Endothelial Cells

Abstract: Heparin affin regulatory peptide (HARP) is an 18-kDa secreted growth factor that has a high affinity for heparin and a potent role on tumor growth and angiogenesis. We have previously reported that HARP is mitogenic for different types of endothelial cells and also affects cell migration and differentiation (12). In this study we examined the signaling pathways involved in the migration and tube formation on matrigel of human umbilical vein endothelial cells (HUVEC) induced by HARP. We report for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
1
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 40 publications
4
119
1
15
Order By: Relevance
“…The present study shows that ERK 1 ⁄ 2 is not involved in PTN-induced cell surface NCL localization, although it is required for PTN-induced endothelial cell migration (26). One possible explanation is that ERK 1 ⁄ 2 may lay downstream of ␣ v ␤ 3 -mediated cell surface NCL localization.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The present study shows that ERK 1 ⁄ 2 is not involved in PTN-induced cell surface NCL localization, although it is required for PTN-induced endothelial cell migration (26). One possible explanation is that ERK 1 ⁄ 2 may lay downstream of ␣ v ␤ 3 -mediated cell surface NCL localization.…”
Section: Discussionmentioning
confidence: 67%
“…To test the hypothesis that PTN-induced cell surface NCL localization depends on ␤ 3 Tyr 773 phosphorylation through RPTP␤/, down-regulation of RPTP␤/ expression in HUVEC by siRNA was performed as previously described (26), and inhibited PTN-induced cell surface NCL localization (Fig. 2E) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MDKD81-121 is able to reduce the formation of capillary-like structures, a crucial step in tumor neovascularization. The effects of MDKD81-121 on HUVEC could be mediated by the inhibition of ALK and/or RPTPb/z tyrosine kinase receptors as HUVECs have been shown to express MDK and both receptors (36,37) enabling the stimulation of the phosphorylation of ALK (36) and the activation of the Akt and ERK pathways (38). We also showed that MDKD81-121 inhibits endothelial cell cycling with a complete extinction of Ki67 expression, while promotes cell apoptosis via activation of a set of genes, including CHOP, implicated in ER stress-mediated apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%